Derivative spectrophotometric methods for determination of dronedarone in pharmaceutical formulation - Ravikumar Vejendla; Male Mahendar; Nancharla Srinath; Gongalla Dilipkumar; T.Naveen Kumar (International Journal of Pharmacy and Analytical Research, 2022)
The objective of this study is to develop a highly, sensitive, derivative spectrophotometric methods has been developed for the determination of Dronedarone hydrochloride in pharmaceutical preparations. The method carried out by using methanol (solvent) ,the optimum results obtained in the measuring wavelength range 240 -310nm.Beer’s law was obeyed in the range of 3.0-20µg/ml. Calibration graphs constructed at their wavelengths of determination were linear in the concentration range of Dronedarone using 3-20 μg.mL-1 (r² = 0.9940, r² = 0.9980, r² = 0.9968 and r²= 0.9975 ) for zero order, first order, second order and third order derivative spectrophotometric method. All the proposed methods have been extensively validated as per ICH guidelines. There was no significant difference between the performance of the proposed methods regarding the mean values and standard deviations. These methods were successfully applied to pharmaceutical formulations because no interferences from tablet excipients were found. The proposed methods were found to be simple, sensitive, accurate, precise, rapid and economical for the routine quality control application of Dronedarone in pharmaceutical formulations.